Implementation Independent Curriculum on Competencies Professionalism of RA Teachers in Bandar Lampung - Dona Dinda Pratiwi; Waluyo Erry Wahyudi; Kuswanto, Cahniyo Wijaya (PELITA NUSA TENGGARA, 2025)
The Independent Curriculum has been officially designated as the national curriculum for the 2024/2025 academic year, as outlined in KMA No. 347 of 2022. However, early childhood Islamic institutions (RA) under the Ministry of Religious Affairs remain underserved in professional training, creating a gap in curriculum readiness. This study aimed to enhance RA teachers’ capacity to implement the Independent Curriculum through a structured mentoring program focusing on curriculum design and teaching module development. Using the Asset-Based Community Development (ABCD) approach, the program engaged 25 RA/PAUD teachers in Bandar Lampung through six online sessions and one offline workshop. The training covered differentiated learning, operational curriculum (KOM) development, and the integration of P5PPRA (Project Strengthening Profile of Pancasila Students and Rahmatan Lil Alamin). Results indicate significant improvement in teachers’ understanding of learner-centered pedagogy, assessment, and the alignment of vision-mission with instructional goals. Two institutions produced complete KOM documents, while others demonstrated partial progress. The program also fostered reflective teaching practices, collaborative planning, and integration of local culture and religious values into instructional design. In conclusion, sustained mentoring can bridge the gap in curriculum implementation at the early childhood level, promote teacher agency, and support systemic transformation aligned with the values of Islamic education. These findings underscore the importance of long-term, context-based professional development for successful curriculum reform.